Heat and shock resistant materials
Patent Information
- Application Number
- JP2020218329
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-28
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-12-28
AI Technical Summary
【0009】 本開示に係る耐熱衝撃性部材は、閉気孔の面積率が10%以上20%以下であるZTAを含み、上記の差(A)が上記の差(B)の0.7倍以上1.3倍以下である。したがって、本開示に係る耐熱衝撃性部材は、ZTAが有する機械的強度および耐熱衝撃性を十分に発揮し得る。
Smart Images

Figure 0007640261000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to thermal shock resistant components. [Background technology]
[0002] Traditionally, ceramics containing aluminum oxide as the main component and zirconium oxide (ZTA) have excellent mechanical strength and thermal shock resistance. Therefore, ZTA is used in firing jigs for firing electronic components such as dielectrics, multilayer capacitors, thermistors, varistors, and chip inductors, welding nozzles, various electric furnace core tubes, support tubes, radiant tubes, gas inlet tubes, gas sampling tubes, thermocouples for temperature measurement, protective tubes for various devices, insulating materials for contact devices, etc.
[0003] As such a ZTA, Patent Document 1 describes an alumina-zirconia sintered body having a tetragonal or cubic zirconia crystal phase and a monoclinic zirconia crystal phase and a porosity (open porosity) of 10 to 40%. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-132577 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0005] The alumina-zirconia sintered body described in Patent Document 1 has a poor balance between the spacing between adjacent pores (open pores) and the spacing between adjacent zirconia particles, and therefore the alumina-zirconia sintered body described in Patent Document 1 cannot fully exhibit its inherent mechanical strength and thermal shock resistance.
[0006] An object of the present disclosure is to provide a thermal shock resistant member that can fully exhibit the mechanical strength and thermal shock resistance of ZTA. [Means for solving the problem]
[0007] The thermal shock resistant member according to the present disclosure includes a ceramic containing aluminum oxide as a main component, zirconium oxide, and an area ratio of closed pores of 10% to 20%. In the ceramic, the difference (A) between the average value of the distance between the centers of gravity of adjacent zirconium oxide crystal particles and the average value of the equivalent circle diameter of the zirconium oxide crystal particles is 0.7 to 1.3 times the difference (B) between the average value of the distance between the centers of gravity of adjacent closed pores and the average value of the equivalent circle diameter of the closed pores.
[0008] The nozzle for welding and cutting or plasma cutting and the insulating member for a contact device according to the present disclosure include the thermal shock resistant member described above. Effect of the Invention
[0009] The thermal shock resistant member according to the present disclosure includes ZTA having an area ratio of closed pores of 10% to 20%, and the difference (A) is 0.7 to 1.3 times the difference (B). Therefore, the thermal shock resistant member according to the present disclosure can fully exhibit the mechanical strength and thermal shock resistance of ZTA. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A thermal shock resistant member according to an embodiment of the present disclosure includes a ceramic that contains aluminum oxide as a main component, contains zirconium oxide, and has an area ratio of closed pores of 10% to 20%. The ceramic having an area ratio of closed pores of 10% to 20% has intermediate properties between dense and porous.
[0011] In this specification, the thermal shock resistant member means a member containing ceramics having a thermal shock resistance temperature of 350° C. or higher obtained in accordance with the precision method specified in JIS R 1648:2002.
[0012] "Aluminum oxide as the main component" means that aluminum oxide accounts for 80% by mass or more of the total 100% by mass of the components constituting the ceramic. The components constituting the ceramic can be identified by an X-ray diffraction device using CuKα radiation. The content of each component can be determined, for example, by an ICP (Inductively Coupled Plasma) emission spectrometer or a fluorescent X-ray analyzer.
[0013] The area ratio of closed pores is measured by the following method. First, the cross section of the ceramic is mirror-polished, and the surface is thermally etched at a temperature of 1420°C and observed at a magnification of 500 times. An average range is selected, and for example, an area of 4.34 × 10 4 μm 2 An image of the area (241 μm in horizontal direction, 180 μm in vertical direction) is taken with a scanning electron microscope to obtain an observation image. The area ratio of closed pores can be determined by particle analysis using this observation image as the subject, using the image analysis software "A-zo-kun (ver2.52)" (registered trademark, manufactured by Asahi Kasei Engineering Co., Ltd.). Hereinafter, when the image analysis software "A-zo-kun" is mentioned, it refers to the image analysis software manufactured by Asahi Kasei Engineering Co., Ltd.
[0014] The setting conditions for this method are, for example, a threshold value, which is an index showing the brightness of an image, of 91, brightness is dark, and the area of small figures to be removed is 1 μm 2 The threshold value can be adjusted according to the brightness of the observed image. The brightness is set to dark, the binarization method is set to manual, and the area of small figures to be removed is set to 1 μm 2 With a noise reduction filter, the threshold value can be adjusted so that the markers appearing in the observed image match the shape of the closed pores.
[0015] When the thermal shock resistant member is a cylindrical nozzle for welding and cutting or plasma cutting, the cross section perpendicular to the axial direction is mirror-polished and the area ratio of open pores is determined according to the method described above.
[0016] The thermal shock resistant member according to one embodiment contains zirconium oxide, which increases the fracture toughness, and as a result, even if the thermal shock resistant member according to one embodiment contains closed pores, it can maintain a certain degree of mechanical strength and absorb stress caused by temperature increases and decreases.
[0017] The content of zirconium oxide is not limited as long as it is an amount containing aluminum oxide as a main component. Zirconium oxide is contained in a ratio of 10 mass% to 15 mass% in a total of 100 mass% of the components constituting the ceramic. When zirconium oxide is contained in a ratio of 10 mass% or more, the fracture toughness of the thermal shock resistant member according to one embodiment can be further increased. When zirconium oxide is contained in a ratio of 15 mass% or less, the decrease in thermal conductivity can be further suppressed.
[0018] The average particle size of the aluminum oxide crystal particles and the zirconium oxide crystal particles is not limited. For example, the average particle size of the aluminum oxide crystal particles is preferably larger than the average particle size of the zirconium oxide crystal particles. With such a configuration, it is more effective to suppress the decrease in the thermoelectric coefficient. The aluminum oxide crystal particles have an average particle size of, for example, about 6 μm or more and 12 μm or less. The zirconium oxide crystal particles have an average particle size of, for example, about 2 μm or more and 4 μm or less.
[0019] To determine the area ratio of closed pores, the average grain size of aluminum oxide crystal grains is determined by drawing six straight lines of the same length, for example 100 μm, radially from an arbitrary point on the observation image. The average grain size can be determined by dividing the length of these six straight lines by the number of crystals present on each line.
[0020] The average particle size of the zirconium oxide crystal grains can be determined by a method called particle analysis using the image analysis software "A-image-kun" for the above observation image. The setting conditions for this method are, for example, a threshold value, which is an index showing the brightness of the image, of 182, brightness of bright, and a small figure removal area of 1 μm 2The threshold value can be adjusted according to the brightness of the observed image. The brightness is set to bright, the binarization method is set to manual, and the area of small figures to be removed is set to 1 μm 2 With a noise reduction filter, the threshold value can be adjusted so that the markers appearing in the observed image match the shape of the zirconium oxide crystal grains.
[0021] In the ceramics contained in the thermal shock resistant component according to one embodiment, the difference (A) between the average value of the distance between the centers of gravity of adjacent zirconium oxide crystal grains and the average value of the equivalent circle diameter of the zirconium oxide crystal grains is 0.7 to 1.3 times the difference (B) between the average value of the distance between the centers of gravity of adjacent closed pores and the average value of the equivalent circle diameter of the closed pores.
[0022] The difference (A) between the average value of the distance between the centers of gravity of adjacent zirconium oxide crystal particles and the average value of the equivalent circle diameter of the zirconium oxide crystal particles is a value indicating the distance between adjacent zirconium oxide crystal particles. The difference (B) between the average value of the distance between the centers of gravity of adjacent closed pores and the average value of the equivalent circle diameter of the closed pores is a value indicating the distance between adjacent closed pores.
[0023] In this way, if the difference (A) is 0.7 to 1.3 times the difference (B), it can be said that the balance between the interval between adjacent zirconium oxide crystal particles and the interval between adjacent closed pores is good. Therefore, even if a thermal shock is applied and microcracks originating from the zirconium oxide or closed pores are generated, the microcracks are unlikely to progress. Therefore, destruction due to cracks generated by thermal shock is suppressed. In order to further suppress destruction due to cracks generated by thermal shock, the difference (A) and the difference (B) may be made approximately the same, for example, the difference (A) may be made approximately 0.9 to 1.1 times the difference (B).
[0024] The average value of the distance between the centers of gravity of the zirconium oxide crystal particles is measured by the following method. Using the image analysis software "A-Image-kun" for the above observation image, the average value of the distance between the centers of gravity of the zirconium oxide crystal particles is obtained by the distance between the centers of gravity method of dispersity measurement.
[0025] The setting conditions for this method are, for example, a threshold value, which is an index showing the brightness of an image, of 182, brightness of light, and a small figure removal area of 1 μm 2 The noise reduction filter can be omitted. The threshold value can be adjusted according to the brightness of the observed image. The brightness can be set to bright, the binarization method can be set to manual, and the small figure removal area can be set to 1 μm 2 With a noise reduction filter, the threshold value can be adjusted so that the markers appearing in the observed image match the shape of the zirconium oxide crystal grains.
[0026] The equivalent circle diameter of the zirconium oxide crystal grains can be obtained by the following method. The equivalent circle diameter of the zirconium oxide crystal grains can be obtained by using the above observation image as the subject, using a method called particle analysis. The setting conditions for this method can also be the same as those used in the centroid distance method for measuring the degree of dispersion.
[0027] The average values of the distance between the centers of gravity of the closed pores and the equivalent circle diameter of the closed pores are measured in the same manner as the average values of the distance between the centers of gravity of the zirconium oxide crystal particles and the equivalent circle diameter of the zirconium oxide crystal particles, except that the set conditions are the same as those used to determine the area ratio of the closed pores.
[0028] The average spheroidization rate of the zirconium oxide crystal particles is not limited. In order to reduce the stress generated at the grain boundaries of zirconium oxide, the average spheroidization rate of the zirconium oxide crystal particles is preferably greater than the average spheroidization rate of the closed pores. The average spheroidization rate of the zirconium oxide crystal particles is preferably, for example, greater than the average spheroidization rate of the closed pores by at least 10%, specifically, by about 14% to 20%. The average spheroidization rate of the zirconium oxide crystal particles may be, for example, 56% to 64%, and the average spheroidization rate of the closed pores may be, for example, 40% to 46%.
[0029] Here, the spheroidization rates of the crystal particles and closed pores of zirconium oxide are the ratios defined by the graphite area method, and are conceptually defined by the following formulas (1) and (2). Spheroidization rate of zirconium oxide crystal particles (%) = (A / B) × 100 (1) A: Actual area of zirconium oxide crystal grains B: Area of the smallest circumscribed circle of a crystal grain of zirconium oxide Spheroidization rate of closed pores (%) = (C / D) × 100 (2) C: Actual area of closed pores D: Area of the minimum circumscribed circle of a closed hole
[0030] Specifically, the average spheroidization rates of the zirconium oxide crystal particles and the closed pores can be determined by a technique called particle analysis using the above-mentioned observation images. However, the set conditions for determining the average spheroidization rate of the zirconium oxide crystal particles are the same as the set conditions used for determining the average distance between the centers of gravity of the zirconium oxide crystal particles. The set conditions for determining the average spheroidization rate of the closed pores are the same as the set conditions used for determining the area ratio of the closed pores.
[0031] If the thermal shock resistant component is a cylindrical nozzle for welding and cutting or plasma cutting, the cross section perpendicular to the axial direction is mirror-polished. The surface is thermally etched at 1420°C, and the average values of the distance between the centers of gravity of the closed pores and zirconium oxide and the circle equivalent diameter are obtained according to the above-mentioned method.
[0032] The ceramics contained in the thermal shock resistant member according to one embodiment may further contain at least one selected from the group consisting of magnesium, calcium, yttrium, and titanium. 2 O 3 and TiO 2 ) act as stabilizers for zirconium oxide. These elements are oxides (MgO, CaO, Y 2 O 3 and TiO 2 ), for example, the total content may be 0.8 mass % or more and 1.2 mass % or less.
[0033] When the total amount is 0.8% by mass or more, the proportion of tetragonal and cubic crystals, which are stable at room temperature, increases in the zirconium oxide crystals. As a result, the mechanical properties such as fracture toughness and mechanical strength of the thermal shock resistant member according to one embodiment can be further improved. When the total amount is 1.2% by mass or less, the occurrence of abnormal grain growth is suppressed. Therefore, the above mechanical properties can be maintained.
[0034] The ceramics contained in the thermal shock resistant member according to one embodiment are composed of at least two selected from the group consisting of lithium, sodium, and potassium oxides (Li 2 O, Na 2 O and K 2 O) may be contained in a total amount of 0.08 mass % or less.
[0035] If the total content is 0.08 mass % or less, the increase in the dielectric tangent (tan δ) can be suppressed. As a result, even if the thermal shock resistant member is used in an environment where temperature variations occur depending on the distribution of plasma, such as a film-forming reaction vessel used in a plasma CVD apparatus, the dielectric tangent (tan δ) is suppressed, so that thermal variations are unlikely to occur. Therefore, the occurrence of cracks is further suppressed.
[0036] The ceramics included in the thermal shock resistant member according to an embodiment may further contain chromium. The amount of chromium contained is not limited, and may be, for example, Cr 2 O 3 This is converted to a content of 0.5 mass % or more and 2.5 mass % or less.
[0037] Chromium is Cr 2 O 3 By including the ceramic in an amount of 0.5% by mass or more and 2.5% by mass or less, the surface of the ceramic included in the thermal shock resistant member according to the embodiment has a pink color, which gives a sense of luxury, aesthetic satisfaction, and a soothing effect to consumers of the thermal shock resistant member according to the embodiment.
[0038] The components that make up the ceramics contained in the thermal shock resistant parts can be identified by the JCPDS card based on the results of measurements using an X-ray diffraction device with CuKα radiation. The ratio of each component can be determined by identifying the components, then calculating the content of the elements that make up the components using an X-ray fluorescence analyzer (XRF) or an ICP emission spectrometer, and converting it into the identified components.
[0039] The heat and shock resistant member may be provided with characters, symbols, figures, logos, marks, QR codes (registered trademark of DENSO WAVE Inc.), etc. These characters, etc. can be obtained by irradiation with laser light. Characters, etc. irradiated with laser light will not disappear even when used at high temperatures (for example, 500°C to 1200°C), and are therefore effective for product management.
[0040] The method for producing the thermal shock resistant member according to the embodiment is not limited, and for example, the thermal shock resistant member can be produced by the following procedure.
[0041] First, aluminum oxide powder and zirconium oxide powder are prepared and mixed to obtain a mixed powder. The purity of these powders is not limited. These powders may have a purity of, for example, 99% by mass or more. The aluminum oxide powder is mixed in a ratio of, for example, 80% by mass or more, and the zirconium oxide powder is mixed in a ratio of, for example, 10% by mass or more and 15% by mass or less, in 100% by mass of the mixed powder.
[0042] If necessary, chromium oxide powder, magnesium oxide powder, calcium oxide powder, yttrium oxide powder, titanium oxide powder, lithium oxide powder, sodium oxide powder, potassium oxide powder, etc. may be blended in a specific ratio. Specifically, chromium oxide powder may be blended in a ratio of 0.5 mass% to 2.5 mass% in 100 mass% of the blended powder, and at least one of magnesium oxide powder, calcium oxide powder, yttrium oxide powder, and titanium oxide powder may be blended in a total ratio of 0.8 mass% to 1.2 mass%. As for lithium oxide powder, sodium oxide powder, and potassium oxide powder, at least these two kinds may be blended in a total ratio of 0.08 mass% or less.
[0043] In addition to these powders, powders that are raw materials for ceramics may also be used, such as powders of silica (silicon dioxide), hafnium oxide, and yttrium oxide.
[0044] Next, these powders and a solvent (e.g., ion-exchanged water, etc.) are put into a grinding mill. Next, the powder is ground until the average particle size (D50) of the powder is 1.5 μm or less, and then an organic binder and a dispersant for dispersing the powder are added and mixed to obtain a slurry. Examples of dispersants include acrylic acid ester copolymers and citric acid. Examples of organic binders include acrylic emulsions, polyvinyl alcohol, polyethylene glycol, and polyethylene oxide.
[0045] The obtained slurry is sprayed and granulated to obtain granules, and then a uniaxial press molding device or a cold isostatic press molding device is used to pressurize the molding pressure at 78 MPa to 160 MPa to obtain a molded body that will be the base of the ceramics, and then cutting is performed as necessary. The molded body is fired in an air atmosphere at 1500°C to 1700°C for 4 hours to 6 hours to obtain ceramics. The obtained ceramics is processed into a desired shape to obtain a thermal shock resistant member according to one embodiment.
[0046] Alternatively, the obtained granules may be filled into a mold corresponding to the shape of the desired thermal shock resistant member to obtain a molded body, and the obtained molded body may be fired to produce a thermal shock resistant member according to one embodiment formed of ceramics. The pressurizing conditions for obtaining the molded body and the conditions for firing the molded body are as described above, and detailed explanations will be omitted.
[0047] Specifically, the ceramics contained in the thermal shock resistant member according to one embodiment were obtained by the following recipe: First, a mixed powder containing about 80.2 mass% aluminum oxide powder, about 12.2 mass% zirconium oxide powder, about 4.7 mass% silicon dioxide powder, about 1.53 mass% chromium oxide powder, about 0.57 mass% magnesium oxide powder, about 0.33 mass% calcium oxide powder, about 0.03 mass% yttrium oxide powder, about 0.06 mass% titanium oxide powder, about 0.05 mass% sodium oxide powder, about 0.01 mass% potassium oxide powder, and other trace components, and ion-exchanged water were charged into a grinding mill.
[0048] Next, the powder was pulverized until the average particle size (D50) was 1.5 μm or less, and then an organic binder (polyvinyl alcohol and polyethylene glycol) and a dispersant (acrylic acid ester copolymer) for dispersing the powder were added and mixed to obtain a slurry. The obtained slurry was spray-granulated to obtain granules, which were then pressurized at about 98 MPa using a uniaxial press molding device to obtain rectangular and cylindrical molded bodies that would become the base for ceramics.
[0049] Next, the obtained molded body was fired in an air atmosphere at the temperature shown in Table 1 for 2 hours to obtain ceramic samples No. 1 to 6. For samples No. 1 to 6, the above-mentioned difference (A) and difference (B) were determined by the above-mentioned measurement method using cylindrical ceramic samples. The area ratio of closed pores for samples No. 1 to 6 was measured by the above-mentioned measurement method. As a result of the measurement, all were 12% or more and 16% or less.
[0050] For Samples No. 1 to 6, the three-point bending strength, which indicates mechanical properties, was measured using samples made of prismatic ceramics in accordance with JIS R 1601: 2005. For Samples No. 1 to 6, the thermal shock resistance temperature, which indicates thermal shock resistance, was measured using samples made of cylindrical ceramics in accordance with the precision method specified in JIS R 1648: 2002.
[0051] For Samples No. 1 to 6, the difference (A), the difference (B), the ratio value (A) / (B), the three-point bending strength, and the thermal shock resistance temperature are shown in Table 1.
[0052] [Table 1]
[0053] As shown in Table 1, samples No. 2 to No. 5, in which the difference (A) is 0.7 to 1.3 times the difference (B), have both high mechanical properties and high thermal shock resistance. On the other hand, sample No. 1, in which the difference (A) is more than 1.3 times the difference (B), has good thermal shock resistance but poor mechanical properties. Sample No. 6, in which the difference (A) is less than 0.7 times the difference (B), has good mechanical properties but poor thermal shock resistance.
[0054] The thermal shock resistant member according to the present disclosure can fully exhibit the mechanical strength and thermal shock resistance of ZTA. Therefore, the thermal shock resistant member according to the present disclosure can be used as a material for, for example, a nozzle for welding or plasma cutting, an insulating member for a contact device, a jig for heat treating electronic components, etc.
Claims
1. The ceramic material contains aluminum oxide as a main component, zirconium oxide, and an area ratio of closed pores is 12% or more and 16% or less, The aluminum oxide crystal particles have an average particle size of 6 μm or more and 12 μm or less, The zirconium oxide crystal particles have an average particle size of 2 μm or more and 4 μm or less, In the ceramic, a difference (A) between an average value of the distance between the centers of gravity of adjacent zirconium oxide crystal grains and an average value of the equivalent circle diameter of the zirconium oxide crystal grains is 0.7 to 1.3 times a difference (B) between an average value of the distance between the centers of gravity of adjacent closed pores and an average value of the equivalent circle diameter of the closed pores. Heat-shock resistant material.
2. 2. The thermal shock resistant member according to claim 1, wherein an average spheroidization rate of the zirconium oxide crystal grains is greater than an average spheroidization rate of the closed pores.
3. 3. The thermal shock resistant member according to claim 1, wherein the zirconium oxide is contained in the ceramic in an amount of 10% by mass or more and 15% by mass or less.
4. The ceramic further comprises chromium, Cr 2 O 3 The thermal shock resistant member according to any one of claims 1 to 3, wherein the content in terms of Cr is 0.5 mass% or more and 2.5 mass% or less.
5. The ceramic further contains at least one selected from the group consisting of magnesium, calcium, yttrium, and titanium, and MgO, CaO, Y 2 O 3 and TiO 2 The thermal shock resistant member according to any one of claims 1 to 4, wherein the total content, calculated as 0.8 mass% or more and 1.2 mass% or less.
6. The ceramic further contains at least two selected from the group consisting of lithium, sodium and potassium, Li 2 O, Na 2 O and K 2 The thermal shock resistant member according to any one of claims 1 to 5, wherein the total content calculated as O is 0.08 mass% or less.
7. A nozzle for welding and cutting or plasma cutting, comprising the thermal shock resistant member according to any one of claims 1 to 6.
8. An insulating member for a contact device, comprising the thermal shock resistant member according to any one of claims 1 to 6.
Citation Information
Patent Citations
Aluminum oxide matrix sintered compact and its production
JP2000128626A
Ceramic member for thermal treatment which has good thermal shock resistance
JP2002128563A
Alumina-zirconia-based ceramic and production method therefor
JP2005239469A
Ceramic fired body and method of manufacturing the same
JP2010202472A
Method for producing alumina sintered compact
JP2011121807A